2012
DOI: 10.1124/mol.111.075457
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Conformations Involved in Dopamine D2LReceptor Functional Selectivity Induced by Selected Transmembrane-5 Serine Mutations

Abstract: Although functional selectivity is now widely accepted, the molecular basis is poorly understood. We have studied how aspects of transmembrane region 5 (TM5) of the dopamine D 2L receptor interacts with three rationally selected rigid ligands (dihydrexidine, dinapsoline, and dinoxyline) and the reference compounds dopamine and quinpirole. As was expected from homology modeling, mutation of three TM5 serine residues to alanine (S5.42A, S5.43A, S5.46A) had little effect on antagonist affinity. All three mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…This is in line with sitedirected mutagenesis studies at position 6.55 in other aminergic GPCRs. These studies revealed the influence of this position on biased signaling related to differential G protein coupling (Tschammer et al, 2011;Fowler et al, 2012). In parallel, the finding that serotonin establishes an interaction with residue S5.46 in helix 5, which is not seen in the dynamic binding profile of 2C-N, could justify the biased nature of the latter.…”
Section: Resultssupporting
confidence: 53%
“…This is in line with sitedirected mutagenesis studies at position 6.55 in other aminergic GPCRs. These studies revealed the influence of this position on biased signaling related to differential G protein coupling (Tschammer et al, 2011;Fowler et al, 2012). In parallel, the finding that serotonin establishes an interaction with residue S5.46 in helix 5, which is not seen in the dynamic binding profile of 2C-N, could justify the biased nature of the latter.…”
Section: Resultssupporting
confidence: 53%
“…the presence of unique sets of scaffolding proteins (Abbas et al, 2009; Becamel et al, 2004). Thus, every ligand interacting with a GPCR may produce its own unique signaling signature in unique cellular contexts (Flordellis, 2012; Fowler et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Using a mutagenic approach, Fowler et al . () have identified the three conserved serine residues on TM5, especially Ser194 5.43 , to be the other major determinants for biased signalling at the D 2L receptor. Further computation analysis has revealed multiple ligand‐specific receptor conformations.…”
Section: Ligand‐specific Receptor Conformations Underlying‐biased Gpcmentioning
confidence: 99%